Peran Guru dalam Pendidikan Anak Hiperaktif di TK Negeri Pembina Pontianak - Riska Ananda Utami; Halida; Lukmanulhakim (Early Childhood Journal, 2025)
This study aims to describe and gain an in-depth understanding of the teacher's role in the education of hyperactive children at TK Negeri Pembina Pontianak Timur. The approach used is qualitative with a phenomenological method, focusing on exploring the teacher's subjective experiences in handling hyperactive children within the school environment. Data collection was conducted through semi-structured interviews with classroom teachers who have experience teaching hyperactive children. The data were analyzed using Colaizzi's method, which includes seven stages of qualitative data analysis. The findings reveal that the teacher's role is not limited to delivering instructional material, but also includes being a facilitator, motivator, and emotional companion for hyperactive children. Teachers strive to adapt their teaching strategies to the children's characteristics, build intensive communication with parents, and create a conducive learning environment. Challenges faced include limited knowledge about children with special needs and a lack of support from school facilities. This study is expected to serve as a consideration for teachers, parents, and educational institutions in developing more effective approaches to educate hyperactive children from an early age.